Optimization of Aloe vera gel in Ficus benghalensis fruit jam for enhanced phytochemical contents and physicochemical properties - Hassan, Ali; Khan, Muhammad Kashif Iqbal; Usman, Ali; Butt, Mubeen Sultan; Fordos, Summaia; Fatima, Iraj; Arif, Sharmeen; Ahmad, Abdul Mueez; Ghazali, Muhammad Hussain (Journal of Pure and Applied Agriculture, 2025)
Ficus benghalensis fruit is known for its high mineral contents, fiber, carbohydrates, and antioxidants, making it an ideal ingredient for preparing functional food products. Aloe vera is a versatile and nutritious ingredient, widely used in food products. F. benghalensis fruit jam with different concentrations of aloe vera gel was made. According to this study, five treatments were prepared T0 control (without aloe vera gel), T1 (5% aloe vera gel), T2 (10% aloe vera gel), T3 (15% aloe vera gel), and T4 (20% aloe vera gel), respectively. Jams were analyzed and characterized by physicochemical analysis, proximate analysis, antioxidant analysis, and total dietary fiber analysis. Results concluded that the addition of aloe vera had significant effect on the pH, titratable acidity, total sugars, and ascorbic acid contents, while non-significant effect on TSS of jam samples was observed. Results showed that aloe vera had a significant effect on carbohydrates, and moisture contents of jam samples, while a non-significant effect on crude fat, fiber, protein and ash contents were observed. Aloe vera gel significantly improved the phytochemicals and dietary fiber contents of jam samples. Future studies can explore the sensory evaluation and shelf-life analysis of Aloe vera-infused F. benghalensis fruit jam to further optimize its production and commercialization.